2021
DOI: 10.7759/cureus.12644
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Total Laparoscopic Hysterectomy: A Single-Surgeon Experience of Initial 50 Cases

Abstract: In this study, we reported a single surgeon experience of total laparoscopic hysterectomy (TLH) in terms of intraoperative and early postoperative outcomes and complications. In addition, we compared our results with published literature for a reevaluation of complications and outcomes. Material and methodsThis present prospective study was conducted on 50 patients who underwent TLH due to benign causes. Patients diagnosed with abnormal uterine bleeding (AUB), uterine fibroids, and post-menopausal bleeding (PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Leiomyomata uteri, abnormal uterine bleeding, endometrial hyperplasia and adenomyosis were the major indications for total laparoscopic hysterectomy. Ashfaq et al reported that the most common indication for TLH was uterine fibroids (54% ) and AUB (36%) [5]. Bilateral salpingo-oophorectomy was done as an additional procedure in more than half of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Leiomyomata uteri, abnormal uterine bleeding, endometrial hyperplasia and adenomyosis were the major indications for total laparoscopic hysterectomy. Ashfaq et al reported that the most common indication for TLH was uterine fibroids (54% ) and AUB (36%) [5]. Bilateral salpingo-oophorectomy was done as an additional procedure in more than half of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cystoscopy after total abdominal hysterectomy was performed in the patient to confirm the closure of the repaired defect. In a study, no bladder injury was reported; however, the number of patients who underwent total laparoscopic hysterectomy was very less [5]. Urologic injuries reported by O'Hanlan et al were less than 3% [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major complications comprised ureteric injury at 1.4%, bladder mucosal injury at 0.05%, port site hernia at 0.02%, and port site infection at 0.08% in the TLH group [ Table 2 ] along with a comparative analysis of the results with other studies [ Table 3 ]. [ 3 4 5 6 7 ]…”
Section: R Esultsmentioning
confidence: 99%